Knowledge-based economy - Michal Wilinski (Institute of Economic Research (IER), 2016)
The purpose of this article is to present a model of knowledge-based economy in relation to the OECD or Organization for Economic Cooperation and Development. The work will be explained the difference between economic growth and economic development. This article aims is to show how the use of factors of knowledge and innovation by the economy affect its faster development. Model presented work shows the extent to which a variable that is known to be action - lovers expressing or measuring knowledge and innovation impact on the economy and the extent to which contributed to its growth, which will be expressed by the Gross Domestic Product.
Keywords: A11; D83; O43; 330; innovation; knowledge; economic development; OECD; KBE